MANAJEMEN LAYANAN PERPUSTAKAAN DIGITAL IKIP PGRI PONTIANAK - Abner, Andrew Melianus; Hanum, Atiqa Nur Latifa; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The results showed that the digital library has implemented management in providing services. In providing services, of course there are basic things to manage a library that has so much library material, and needs expertise in operating it. However, in its operation, management still experiences obstacles, namely circulation services, internet access and websites, however, management is open to criticism and suggestions that can be accessed via email which has been included in the IKIP PGRI Pontianak digital library. This research is to describe service management in the digital library at IKIP PGRI Pontianak. The focus of this research is on the management aspects of IKIP PGRI Pontianak digital library services, especially on service management procedures in the digital library owned by IKIP PGRI Pontianak. By using qualitative methods with data collection techniques through observation, interviews and using documentation, the research subjects interviewed were 7 informants in the IKIP PGRI library as well as IKIP PGRI Pontianak students or outside students who had accessed the IKIP PGRI Pontianak digital library.